IDPs of East Beirut versus the Lebanese State - Lteif, D (Refugee Studies Centre, University of Oxford, 2019)
This year marks the thirtieth anniversary of the Taif agreement that formally ended the Lebanese Civil War of 1975–1990. Three decades later, some communities remain internally displaced because of the actions of the State.